Regional Node Distribution in Papillary Thyroid Cancer with Microscopic Metastasis. (1st November 2018) - Hurtado-López, Luis-Mauricio; Ordoñez-Rueda, Alejandro; Zaldivar-Ramírez, Felipe-Rafael; Basurto-Kuba, Erich
Abstract : Background . Optimal neck lymphadenectomy in patients with papillary thyroid cancer (PTC) and microscopic lymph node metastasis needs to be defined in order to aid surgeons in their decision about the best way to proceed in these cases. Methods . Patients who underwent total thyroidectomy and lymphadenectomy at levels IIa to VI were divided into two groups: Group 1 (G1) with macroscopic metastasis detected before surgery and Group 2 (G2) with microscopic metastasis detected in sentinel node during surgery. Odds ratio (OR) was computed for age, sex, tumor size, multicentricity, capsular invasion, vascular/lymphatic permeation, and nodes with metastasis. Results . Primary tumor size was (G1 versus G2, respectively) 3.8 cm versus 1.98 cm (P<0.001); only lymphatic permeation was correlated to an increase in metastasis in lymph nodes 65.4% versus 25% (OR=5.6, p<0.001); metastatic frequency by region was IIa 18.5% versus 1.5%, III 24.3% versus 9.9%, IV 17.4% versus 18.1%, and VI 25.9% versus 71, 2%. Metastasis to level V was found only in G1. Conclusion . Selective lymphadenectomy at levels III, IV, and VI is optimal for PTC patients without preoperative evidence of lymph node disease, but who present with lymph node microscopic metastasis in an intraoperative assessment.